An Analysis of External Conflicts in Joker Movie - Tue, Elisabeth Aderani Savera; Resen, I Wayan; Winarta, I Bagus Gde Nova (Institut Pariwisata dan Bisnis Internasional, 2023)
This study aims to identify knowledge about literary studies, especially the intrinsic elements of a literary work, which is limited to the type of external conflict in Todd Philips' Joker movie. The formulation of the problem in this study are (1) How does the character resolve the conflict in the Joker movie. This study uses a quantitative and qualitative descriptive method to provide a clearer picture of the problem under study. The data from this study were taken using the observation method through four stages, namely watching the Joker movie. Then, find and record the type of external conflict spoken by the characters in Joker movie. Reading the Joker movie script and finally, the writer categorizes the analysis of the types of data findings based on the type of external conflict. There is only one type of external conflicts found, namely man against man. The types of external conflicts can be distinguished based on the data found. The results show that there are 3 types of external conflicts found in the Joker movie.